2022
DOI: 10.31557/apjcp.2022.23.5.1627
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Women’s Participation in Breast Cancer Screening in Turkey

Abstract: Community-based and standardized mammography screening can reduce breast cancer mortality by 25% in the 50-69 age group and by 40% in the 40-69 age group (WHO, 2008). Cancer Early Diagnosis, Screening and Education Centers (KETEM) were established in early 2000's in Turkey to carry out community-based screening programs for cancers which WHO recommends being screened. Cancer screening services are provided free of charge. According to the National Standards of Breast Cancer Screening Program In Turkey, women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…These factors included primigravida status, fear of pain, and a lack of privacy. These ndings align with previous studies that had discussed the in uence of fear of pain, shyness, and privacy on women's participation in research (19,20). However, our study uniquely identi ed primigravida as a factor.…”
Section: Discussionsupporting
confidence: 90%
“…These factors included primigravida status, fear of pain, and a lack of privacy. These ndings align with previous studies that had discussed the in uence of fear of pain, shyness, and privacy on women's participation in research (19,20). However, our study uniquely identi ed primigravida as a factor.…”
Section: Discussionsupporting
confidence: 90%
“…It was reported that the community-based and standardized mammography screening can reduce breast cancer deaths by 25% in the age group of 50–69 years and by 40% in the age group of 40–69 years. Mammography screening is performed every two years for women aged between 40 and 69 years by following the National Standards of the Breast Cancer Screening Program in order to achieve early diagnosis in Türkiye [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to motivate women’s involvement in screening, national and institutional policies should be developed and implemented to address their concerns and sociocultural barriers. 87 …”
Section: Methodsmentioning
confidence: 99%
“…In order to motivate women's involvement in screening, national and institutional policies should be developed and implemented to address their concerns and sociocultural barriers. 87 Psychological therapies frequently call for the patient's participation and dedication. For this kind of participation, it is required that the patient be motivated.…”
Section: The Fifth Principlementioning
confidence: 99%